Probiotic-fermented blueberry juice prevents obesity and hyperglycemia in high fat diet-fed mice in association with modulating the gut microbiota. Issue 10 (8th October 2020) - Zhong, Hao; Abdullah,; Deng, Lingli; Zhao, Minjie; Tang, Jun; Liu, Tao; Zhang, Hui; Feng, Fengqin
Abstract : Fermented blueberry juice intervention has demonstrated remarkable potential against obesity and type 2 diabetes mellitus. Abstract : Blueberry dietary interventions have demonstrated remarkable potential against obesity and type 2 diabetes mellitus. However, the effects of fermented blueberry juice on metabolic syndrome, the gut microbiota, and insulin resistance have not yet been reported. This study aimed to investigate the potential of fermented blueberry juice against obesity, hyperglycemia, and gut microbiota dysbiosis in high fat diet (HFD)-fed mice. Our study findings revealed that supplementation with fresh blueberry juice (BBJ), and fermented blueberry juice with homemade probiotic starter (FBJ) or commercial starter (CFBJ) significantly decreased fat accumulation and low density lipoprotein cholesterol (LDL-C) levels in HFD-fed mice. FBJ showed relatively more potency to reduce body weight than BBJ and CFBJ. The percentage increase in the body weight of the FBJ group was almost the same as that in the normal chow diet (NCD) group, and was approximately 10% lower than the BBJ and CFBJ groups. Overall, all blueberry juices significantly ameliorated hyperlipidemia and insulin resistance in HFD-fed mice. Moreover, the dietary interventions with BBJ, FBJ, and CFBJ for 17 weeks significantly improved the community richness and diversity of the gut microflora along with an altered structure in the HFD-fed mice group. The FBJ treated mice group showed relatively low abundance of Firmicutes, obesity-related bacteria ( Oscillibacter and Alistipes ), and high abundance of lean bacteria ( Akkermansia, Barnesiella, Olsenella, Bifidobacterium, and Lactobacillus ) compared to the HFD-fed mice group. Furthermore, BBJ and FBJ treatments regulated the liver mRNA and protein expression levels involved in lipid and glucose metabolism. This study inferred that fermented blueberry juice could be used as a functional food to prevent the modern pandemics i.e., obesity and insulin resistance.